2011
DOI: 10.1161/atvbaha.111.229302
|View full text |Cite
|
Sign up to set email alerts
|

Arginase I Attenuates Inflammatory Cytokine Secretion Induced by Lipopolysaccharide in Vascular Smooth Muscle Cells

Abstract: Objective-Inflammation plays an important role in atherosclerosis. Arginase I (Arg I) promotes the proliferation of vascular smooth muscle cells; however, the effect of Arg I on inflammation remains unknown. The present study investigated the role of Arg I in inflammation in vitro and in vivo. Methods and Results-Quantitative reverse transcription-polymerase chain reaction and Western blot analysis demonstrated that Arg I inhibited tumor necrosis factor-␣ production induced by lipopolysaccharide in human aorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 25 publications
2
33
1
Order By: Relevance
“…5 Previous studies have shown that Arginase1 can serve as an unexpected beneficial role of Arginase1 in inflammatory diseases such as atherosclerosis. 36 However, the anti-inflammatory effect of Arginase1 in the CNS has not been reported. We demonstrate that the suppression of either Jmjd3 or Arginase1 can enhance NO production in a similar manner; however, introduction of full-length Arginase1 into Jmjd3-knockdown cells could suppress the NO elevation and attenuate neuron death.…”
Section: Discussionmentioning
confidence: 99%
“…5 Previous studies have shown that Arginase1 can serve as an unexpected beneficial role of Arginase1 in inflammatory diseases such as atherosclerosis. 36 However, the anti-inflammatory effect of Arginase1 in the CNS has not been reported. We demonstrate that the suppression of either Jmjd3 or Arginase1 can enhance NO production in a similar manner; however, introduction of full-length Arginase1 into Jmjd3-knockdown cells could suppress the NO elevation and attenuate neuron death.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with advanced atheroma, this might have a destabilizing impact on plaque, inasmuch as increased expression of arginase I is reported to have a stabilizing impact in that regard (Wang et al 2014;Teupser et al 2006;Wang et al 2011). Conceivably, this might help to explain why a controlled trial of arginine supplementation (9 g daily) large and long enough (6 months) to report hard endpoints, enrolling patients who had recently suffered a myocardial infarct, observed six deaths in the treatment group, versus zero in those receiving placebo (P = 0.01); as a result, the trial was terminated sooner than planned (Boger 2008;Schulman et al 2006).…”
Section: A Note On Argininementioning
confidence: 99%
“…Ex vivo EPR studies on aortic rings also showed absence of an O 2 •-signal in response to AngII in EBP50 KO, correlating with findings in Nox1 KO. Moreover, in vivo data demonstrated that in response to another robust inducer of Nox-derived ROS, LPS (27)(28)(29)(30)(31)(32)(33), vascular medial smooth muscle oxidation was absent in EBP50 KO mice. Because Nox1 is a major source of O 2…”
Section: Discussionmentioning
confidence: 98%
“…Mice were subjected to vehicle or lipopolysaccharide (LPS) (10 mg·kg −1 , i.p. ; 16 h), another well-established activator of ROS and Nox activity (27)(28)(29), including Nox1 (30-33), the major Nox in the media of conduit arteries (1,2,22). Femoral arteries from these mice were isolated, sectioned, and stained for 4-hydroxynonenal (4-HNE, a footprint marker of lipid oxidation and oxidative stress).…”
Section: Angiimentioning
confidence: 99%